Long-term residential care in Ireland: Developments since the onset of the COVID-19 pandemic - Brendan Walsh; Sheelah Connolly (The Economic and Social Research Institute (ESRI), 2024)
Long-term residential care (LTRC) is a key component of health and social care in Ireland. Prior to the pandemic, over 32,000 people used LTRC. As the population grows, especially at older ages, the importance of a LTRC sector that meets the needs of the population increases. The COVID-19 pandemic had a significant impact on the LTRC sector in Ireland and internationally. LTRC residents saw high rates of COVID-19 infection and disproportionately high rates of deaths from COVID-19. At the same time, the pandemic also presented a number of challengesfor LTRC workers, operators and regulators. These challenges may inhibit the sustainability of the sector. The aim of this report is to examine how COVID-19 impacted the LTRC sector, and the changes in the sector that occurred since the onset of the pandemic. This report is one of a number of outputs from a Research Collaborative in Quality and Patient Safety (RCQPS) funded project1 that examines LTRC and COVID-19 in Ireland. The report will set the scene for later work which seeks to provide recommendations to help ensure the sustainability of the LTRC sector in the medium term.
Keywords: 330; Pflegeheim; Branchenentwicklung; Epidemie; Coronavirus; Irland